Labor Market Transformation and Demand for a New Type of IT Specialists in Digital Economy Trend - Svetlana D. Nadezhdina; Olga A. Chistyakova; Alexey A. Chistyakov (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
The article presents the main trends of the labor market in terms of the demand for a new type of IT specialists in the digital economy. The article forms a comprehensive understanding of the trends in the IT specialists’ labor market development in the context of the digital economy transformation and trends’ interaction with educational institutions through the acquisition of new professional competencies. To determine the relevance of the topic and identify key objectives, the authors performed a multidimensional bibliometric analysis of publication activity using six basic terms and their combinations. The article presents a statistical review of the IT personnel number in the world and Russia, the changes in the employment forms and the requirements for professional competencies in accordance with the Industry 4.0 paradigm, and confirms the hypothesis of insufficient flexibility and adaptability of the higher education system in terms of requests for a new type of IT specialists. The authors confirm the necessity for transforming the labor market and adapting to new realities on the part of both IT companies and specialists in the field. The study serves as a prerequisite for forecasting personnel needs and identifying structural changes in the digital skills of information and computer technology workers.